2018
DOI: 10.1016/j.ajpath.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Mediated Autophagy Promotes Beclin1 Degradation in Persistently Infected Hepatitis C Virus Cell Culture

Abstract: Liver cirrhosis is an independent risk factor for hepatocellular carcinoma (HCC). The mechanisms that contribute to HCC development in the cirrhotic microenvironment are unknown. We found that HCC grown in the highly stressed cirrhotic microenvironment undergoes autophagy switching from a protective state characterized by high macroautophagy with low chaperone-mediated autophagy (CMA) to an HCC-promoting state characterized by low macroautophagy with high CMA. This study examined how the stress response execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 69 publications
(56 reference statements)
4
21
0
Order By: Relevance
“…110 Using the HCV cell culture model, we showed that excessive ER stress activates NRF2-mediated autophagy switching to promote cell survival. 111 The excessive stress contributes to HCC development in liver cirrhosis. HCC grown in the cirrhotic liver undergoes autophagy switching from a protective state characterized by high macroautophagy with low CMA to an HCC-promoting state characterized by low macroautophagy with high CMA.…”
Section: Hepatocytes In the Liver Undergo Pathological Adaptation To mentioning
confidence: 99%
See 1 more Smart Citation
“…110 Using the HCV cell culture model, we showed that excessive ER stress activates NRF2-mediated autophagy switching to promote cell survival. 111 The excessive stress contributes to HCC development in liver cirrhosis. HCC grown in the cirrhotic liver undergoes autophagy switching from a protective state characterized by high macroautophagy with low CMA to an HCC-promoting state characterized by low macroautophagy with high CMA.…”
Section: Hepatocytes In the Liver Undergo Pathological Adaptation To mentioning
confidence: 99%
“…We showed that HCV induces impaired autophagy response to inhibit degradation of EGFR at the level of autophagosome-lysosome fusion leading to the activation of downstream RAS/RAF/MEK/ERK signaling. 111 In principle, impaired autophagy due to HCV could potentially stabilize RTK on the cell surface of infected cells by impairing their endocytosis and lysosomal degradation. Other researchers have also shown that EGFR activation favors the HCV entry process through co-internalization of an HCV-CD81-EGFR complex following binding of EGFR ligands to the receptor and subsequent endocytosis.…”
Section: Receptor Tyrosine Kinases (Rtks)mentioning
confidence: 99%
“…In addition to non-canonical p62/Nrf2 activation pathway, Nrf2 is strongly induced by ER and oxidative stress in persistently HCV-infected cells. Among Nrf2 target genes, Hsc70 and LAMP2 are upregulated in their transcription, consequently activating CMA (Aydin et al, 2018). The activation of CMA leads to lysosomal degradation of both pro-autophagic protein BECLIN 1, thus impairing autophagy, and the tumor suppressor p53 (Aydin et al, 2017(Aydin et al, , 2018.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Among Nrf2 target genes, Hsc70 and LAMP2 are upregulated in their transcription, consequently activating CMA (Aydin et al, 2018). The activation of CMA leads to lysosomal degradation of both pro-autophagic protein BECLIN 1, thus impairing autophagy, and the tumor suppressor p53 (Aydin et al, 2017(Aydin et al, , 2018. Accordingly, it has been shown that HCV replication is able to suppress p53 functions and that p53 protein levels are low in HCV-infected explanted livers (Aydin et al, 2017).…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…In the autophagy context, it is important to underline that, together with the canonical (ROS-dependent, KEAP1-dependent) and non-canonical (p62-dependent) mechanisms of NRF2 activation, endoplasmic reticulum (ER) stress represents an additional connection between autophagy and Nrf2 [ 143 , 144 ]. Indeed, eukaryotic translation initiation factor 2 alpha kinase 3 (PERK), a type I ER transmembrane protein which participates in the regulation of the Glucose regulatory protein 78 (GRP78) [ 145 ], in response to proteins accumulated in the ER lumen, is separated from Keap1 and phosphorylates Nrf2 [ 146 ], allowing its nuclear translocation, and activation of cell survival signals. Accordingly, persistent HCV replication in liver cirrhosis has been shown to activate NRF2 phosphorylation and nuclear translocation, suggesting that the PERK pathway could directly contribute to cell survival through NRF2 phosphorylation and to HCC development [ 147 ].…”
Section: Mechanisms Of Nrf2 Activation In Hccmentioning
confidence: 99%